(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study investigates the complex nature of phonotactics and its manifestation across segmental units in language systems. The research examines both theoretical frameworks and practical implications of phonotactic constraints in various languages, analyzing how different phonological systems organize sound combinations. Particular focus is given to the integration of articulatory phonetics, phonological theory, and typological analysis in understanding phonotactic patterns. The study identifies key aspects of phonotactic organization, including syllable structure constraints, sonority sequencing principles, segmental co-occurrence restrictions, and the psychological reality of phonotactic knowledge in native speakers’ linguistic competence.